A prospective study of postpartum insertions of intrauterine contraceptive device in a tertiary care hospital - Kumar, Priya; Indrani, Chaitanya; Nagaraju, Karunya; Narayanappa, Dharmavijaya Mathigatta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: We are facing a major challenge due to unmet need for contraception in the postpartum period. Inspite of many available contraceptives numerous unplanned pregnancies occur. Though the couples desire contraception, they are not able to accept it due to their ignorance and misconception. Postpartum IUCD insertion is an effective way to counter this. This study was planned to build up data for acceptance, safety and to identify the reasons for non-acceptance and follow up of postpartum IUCD insertions and the challenges faced. Methods: The present study is a prospective study which was conducted in MVJMC&RH over a period of 1 year which included 397 participants and they were followed up for a period of 6 months at two intervals. Reasons for acceptance and refusal of PPIUCD was recorded, and all issues were addressed along with routine postnatal care. Results: In the study period of one year there were total of 397 deliveries and 235 insertions. Out of them acceptance rate was 59.19%. Follow up was done at 6 weeks and 6 months. A follow up of 66.8% at 6 weeks and 51.9% at 6 months was noted. Expulsion rates were 2.9% at 6 weeks and 1.7% at 6 months follow up. Conclusions: This study shows that a steadfast commitment to postpartum contraception by health care providers and the government will unquestionably lessen incidence of unintended pregnancies and the accompanying burden which is a need of the hour to our booming nation.